Lekarniški farmacevt in bolezni ušes, nosu in grla - Cvirn Novak, Mateja (Farmacevtski vestnik, 2012)
The inflammation of ear, nose, and throat is common disease and patients very frequently address the community pharmacists to help them. Based on collected information regarding the patient disease pharmacist can decide whether the patient can be self-treated or he/she needs to visit the doctor. Protocols forself-treatment are a useful tool to lead the patient during self-treatment process. This article reviews the medicinal products chosen for self-treatment of the inflammation of ear, sore throat and runny nose. Patient susing medicinal products for the chronic treatment of uninfectious diseases need medicinal product usage review. In this way patient therapy can be judged and appropriateness of self-treatment medicinal products can be assessed with the purpose to prevent complications and drug interactions. In patients that report difficulties connected to the medicinal products difficulties must be detected. Appropriate measures should be taken.
Keywords: grlo; lekarništvo; nos; samozdravljenje; uho; vnetja